O6 alkylguanine-DNA alkyltransferase activity in human myeloid cells. - Gerson, S L (1985)
The association between alkylating agent exposure and acute nonlymphocytic leukemia in humans indicates that myeloid cells may be particularly susceptible to mutagenic damage. Alkylating agent mutagenesis is frequently mediated through formation and persistence of a particular DNA base adduct, O6alkylguanine, which preferentially mispairs with thymine rather than cytosine, leading to point mutations. O6alkylguanine is repaired by O6alkylguanine-DNA alkyltransferase (alkyltransferase), a protein that removes the adduct, leaving an intact guanine base in DNA. We measured alkyltransferase activity in myeloid precursors and compared it with levels in other cells and tissues. In peripheral blood granulocytes, monocytes, T lymphocytes, and B lymphocytes, there was an eightfold range of activity between individuals but only a twofold range in the mean activity between cell types. Normal donors maintained stable levels of alkyltransferase activity over time. In bone marrow T lymphocytes and myeloid precursors, there was an eightfold range of alkyltransferase activity between donors. Alkyltransferase activity in the two cell types was closely correlated in individual donors, r = 0.69, P less than 0.005, but was significantly higher in the T lymphocytes than the myeloid precursors, P less than 0.05. Liver contained the highest levels of alkyltransferase of all tissues tested. By comparison, small intestine contained 34%, colon 14%, T lymphocytes 11%, brain 11%, and myeloid precursors 6.6% of the activity found in liver. Thus, human myeloid precursors have low levels of O6alkylguanine-DNA alkyltransferase compared with other tissues. Low levels of this DNA repair protein may increase the susceptibility of myeloid precursors to malignant transformation after exposure to certain alkylating agents.